Product-service systems business models for circular supply chains. Issue 6 (26th April 2018) - Yang, Miying; Smart, Palie; Kumar, Mukesh; Jolly, Mark; Evans, Steve
Abstract: Shifting supply chains from linear to closed-loop models is an important step towards circular economy. This paper investigates business model innovation for circular supply chains, and proposes that product-service systems (PSS) business models can enhance the circularity of supply chains through value creation in inner circles, circling long and cascading use circles. It adopts an exploratory case study method of a large Chinese manufacturing firm operating a traditional product-based business model and three types of PSS business models (i.e. product-, use- and result-oriented PSSs). The supply chain operations of the four distinct business models are analysed and their associated circularities are discussed. The findings show that business models akin to result-oriented PSS, have tighter and more efficient cycles of supply chain operations; which means, the repair, reuse and remanufacturing system is faster and the rate is higher. This research contributes to a better understanding of the relationship between business model innovation and supply chain circularity.